A review on gasification and pyrolysis of waste plastics - Shah, Hamad Hussain; Amin, Muhammad; Iqbal, Amjad; Nadeem, Irfan; Kalin, Mitjan; Soomar, Arsalan Muhammad; Galal, Ahmed M. (Frontiers in Chemistry, 2023)
Gasification and pyrolysis are thermal processes for converting carbonaceous substances into tar, ash, coke, char, and gas. Pyrolysis produces products such as char, tar, and gas, while gasification transforms carbon-containing products (e.g. the products from pyrolysis) into a primarily gaseous product. The composition of the products and their relative quantities are highly dependent on the configuration of the overall process and on the input fuel. Although in gasification, pyrolysis processes also occur in many cases (yet prior to the gasification processes), gasification is a common description for the overall technology. Pyrolysis, on the other hand, can be used without going through the gasification process. The current study evaluates the most common waste plastics valorization courses for producing gaseous and liquid products, as well as the key process specifications that affected the end final products. Reactor type, temperatures, residence time, pressure, fluidizing gas type, flow rate and catalysts were all investigated in this paper. Pyrolysis and waste gasification, on the other hand, are expected to become more common in the future. One explanation for this is that public opinion of incineration of waste in some countries are a main impediment to the development of new incineration capacity. However, an exceptional capability of gasification and pyrolysis over incineration to conserve waste chemical energy is also essential.